Spiritual Wholeness for Clergy: A New Psychology of Intimacy with God, Self, and Others - Hands, Donald R.; Fehr, Wayne L. (Rowman & Littlefield Publishers, 1994)
The authors combine clinical psychology and spiritual direction to create a practical model of spirituality that integrates theology, psychology, and an understanding of individual frailties in a new way. Spiritual Wholeness draws on counseling experience with more than 400 clergy and pinpoints the human problems, traps, and temptations awaiting those who choose the clergy role. Clergy will learn to develop and maintain a psychologically healthy spirituality in relationships with others. Judicatory executives and therapists working with clergy will gain insight into addiction problems and how to help clergy move toward greater emotional and spiritual health.